From Dimensions to Strategy: Analysis of Food Security Factors for the Formulation of the Ciamis Regency Food Security Strategy - Syakirotin, Muthiah; Nur Amalia, Lidya; Setiawan, Perdi; Siti Nur Anisah, Siti Nur; Gandara, Yoga; Hasbilah, Nazril; Putri, Susi Amelia (Jurnal Agriuma, 2025)
This study examines the relationship between food security dimensions availability, accessibility, and utilization—and the composite food security index of farmer households in Panawangan Subdistrict, Ciamis Regency. A mixed-method approach with multiple linear regression analysis was employed. The results show an average household income of IDR 7,657,162 per month, mainly from non-farm sources (51%), with food expenditure accounting for 33% of total spending and energy consumption reaching 82% (moderate level). Most households were classified as food secure. The regression model explained 94.8% of the variation in household food security (R² = 0.948), with food availability as the dominant factor, followed by accessibility, while utilization had a positive but insignificant effect. These findings highlight the critical role of food availability and accessibility as the main determinants of household food security, while utilization remains weak.